Morphological status of the liver of offspring born from mothers with toxic liver lesions - D.B. Adilbekova (Zien Journals, 2024)
Chronic toxic damage to the mother's liver negatively affects the processes of postnatal development and the formation of the offspring's liver. In the vascular-tissue structures of the liver of the offspring in the early periods of postnatal development, inflammatory-reactive and dystrophic changes are observed. These morphological changes in the liver of the offspring subsequently led to a slowdown and lag in the rate of growth and development and formation of the vascular-tissue structures of the liver of the offspring, compared to the offspring of control intact animals.
Keywords: chronic toxic hepatitis; mother-offspring; liver